The establishment of a skills and development training framework for municipal frontline staff : the case of the City of Tshwane - Holtzhausen, Natasja (University of Pretoria, 2018)
South Africa is a developmental state; therefore, various skills and capabilities are required to achieve the country’s developmental goals. Municipalities form the sphere of government that is closest to the citizens of the country, and as such they are at the forefront of public service delivery as they provide services to the citizens on a daily basis. Legislation is in place to ensure that services are delivered in an effective and efficient manner and that these services are of a high quality. However, this is not always the case, as is evidenced by the dissatisfaction experienced by the citizens. Citizens increasingly voice their frustration and dissatisfaction with the level of municipal services received. The municipal frontline staff are at the coalface of service delivery: they are often the only contact that citizens have with government and, therefore, citizens regard frontline staff as the face of government. Because the needs of citizens have changed and are still changing, municipalities require an agile and flexible workforce who have the skills, knowledge, competencies, attitudes and behaviours to adapt to changing needs. The municipal frontline staff (or customer care consultants, as they are referred to in the City of Tshwane Metropolitan Municipality) are expected to provide efficient, effective and professional services. Training plays an important role in ensuring that they are able to deliver the services that citizens expect and that service delivery legislation requires. Legislation on training that has been enacted in South Africa influences the manner in which training is implemented and assists municipal frontline staff in honing the requisite knowledge, skills, competencies, attitudes and behaviours. The literature review revealed that training could assist the customer care consultants to gain these skills and enable them to deliver services efficiently, effectively and professionally. Therefore, municipal frontline staff should be trained to ensure that the developmental goals of local government are reached.